Crip theory and the disabled identity: why disability politics needs impairment - Jenks, Andrew (Disability & Society, 2019)
This article highlights the importance of recognizing both the ontology of impairment as it relates to the creation of the disabled identity as well as why articulations of the disabled identity being ‘crip’ obfuscate potential politics. Examining how the disabled identity has been cast as a coherent social and political category, rather than the messy and complicated identity it truly is, I argue the adoption of a post-structuralist orientation by activists and advocates is bad for disability politics. Providing two examples, the first focusing on a publicized rape case of a person with an intellectual disability and the second on the importance of disability rights claims based on visibility of impairment, I show how articulations like those made in crip theory can have serious, negative implications for the lived experience of people with disabilities. I conclude with a call for disability studies scholars to engage disability politics in their work.
Keywords: 2000 à aujourd'hui; 2010-2019; activisme; approches et analyses; capacitisme; care; corps; cours; crip; discipline; droit; droit des personnes en situation de handicap; histoire et politique; justice sociale; postmodernisme; premier cycle; périodes historiques; ressource en ligne; santé; science politique; science politique et droit; sex1920; systèmes d'oppressions; thématiques; études critiques du handicap

Displaying Families - Finch, Janet (Sociology, 2007)
This article argues that the sociology of contemporary family relationships should be developed to recognize the importance of ‘displaying’ as well as ‘doing’ family. The addition of the concept of ‘display’ to the sociological tool kit is not only a necessary complement to the important conceptual developments which have taken place in recent years, but is also rich in its potential for further empirical and theoretical work. In developing this theme, the article examines empirical evidence from recent UK studies of family relationships, exploring why ‘display’ is important in contemporary family relationships as well as the process through which it occurs. The article represents an initial exploration of these themes. The author's principal aim is to open up this aspect of family life for debate within the relevant sociological research community, encouraging others to refine the concept as well as to use it.
Keywords: 2000 à aujourd'hui; 2000-2009; angleterre; approches et analyses; care; cours; discipline; europe; famille; hétérosexualité; maternité; postmodernisme; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexualité; soc2264; sociologie; thématiques

Innovation technologique et pratiques domestiques : analyse d'une expérience domotique - Beillan, Véronique (Sociétés contemporaines, 1994)
À partir du suivi sociologique d'une expérience domotique portant sur quinze logements du secteur HLM, cette étude traite des conditions d'appropriation sociale d'une nouvelle technologie domestique. Après un exposé de la méthode de recueil des données, basée sur la réalisation de trois vagues ď entretiens - réparties sur trois ans - auprès des ménages du lotissement domotique, l'article présente les premiers résultats ainsi que les nouvelles pistes de recherche à approfondir lors de la troisième et dernière phase du suivi. L'analyse comparative des deux premières vagues d'entretiens a permis de noter la permanence des attentes et des attitudes des ménages à l'égard de la domotique mais aussi le caractère hétérogène et ambivalent de ces dernières. Des freins ď ordre socio-économique et socio-culturel à l'intégration sociale de la technique ont été identifiés. Ainsi, des liens se dessinent entre l'automatisation des tâches et certains éléments tels que le statut et l'identité de la femme, l'organisation et la hiérarchisation des activités domestiques, les pratiques de délégation et ď externalisation du travail domestique.
Number: 1
Keywords: 1900-1999; 1980-1989; 1990-1999; approches et analyses; care; cours; discipline; europe; france; inégalités; postmodernisme; premier cycle; périodes historiques; régions géographiques; sciences humaines; soc2051; sociologie; systèmes d'oppressions; thématiques; travail; travail domestique

Love and Intimacy: The Gender Division of Emotion and 'Emotion Work': A Neglected Aspect of Sociological Discussion of Heterosexual Relationships - Duncombe, Jean; Marsden, Dennis (Sociology, 1993)
This paper discusses the role of ideologies of love and intimacy in heterosexual coupledom, and examines the applicability of theories of the gender division of 'emotion work' to the field of intimate personal relationships. Research on the private sphere of the family has recently focused on quantifying instrumental aspects of relationships, such as financial management, the domestic division of labour and informal care. However, although fruitful, such approaches neglect the expressive or emotional; particularly the experiences of love and intimacy, which many people say they regard as a key element in their personal relationships. We suggest reasons for British sociology's neglect of what is almost a cliche in everyday discourse. And we present evidence (including preliminary findings from our own research on heterosexual couples) that - despite dissatisfaction with gender inequalities in domestic tasks and finance - many women express unhappiness primarily with what they perceive as men's unwillingness or incapacity to `do' the emotional intimacy which appears to them necessary to sustain close heterosexual couple relationships. We illustrate how similar discussions of gender differences in emotional behaviour have emerged elsewhere (including in the new masculinity literature), raising questions about how far men's and women's emotional behaviour can and should change.; The exploration of socially-regulated or `managed' gender divisions in intimate emotional behaviour entails two related but distinct questions: are men and women equally `susceptible' to the emotions or discourses of love and intimacy; and, do they handle such emotions in similar ways in the context of close personal relationships. We suggest how research findings on heterosexual couple relationships can be linked to work on the social regulation of emotion, which argues that there is a `gender division of emotion work' where it is assumed that women will take responsibility for the management of emotion in the private sphere.
Keywords: 1900-1999; 1980-1989; angleterre; approches et analyses; care; cours; discipline; emotional labor; europe; hétérosexualité; postmodernisme; premier cycle; périodes historiques; relations amoureuses; régions géographiques; sciences humaines; sexualité; soc2264; sociologie; thématiques; travail